Managing your own learning - Davis, James R., 1936- (Berrett-Koehler Publishers ; [Distributed by] Publishers Group West, 2000)
In today's knowledge-based society, where intellectual capital is an organization's most competitive asset, learning is serious business. Effective Training Strategies offers a comprehensive approach to creating a focused philosophy of learning, choosing the best approach to planning programs and activities, and developing appropriate systems for assessing results. Davis and Davis describe seven powerful training strategies.